en
utf-8
math math-format graphie
Inverse of linear function
fu-03-02
radio
60
randRangeNonZero(-3, 3) randRangeNonZero(-5, 5) coefficient(M) + "x" coefficient(B) + "x" fractionVariable(1, M, "x") fractionVariable(-1, M, "x") M < 0 ? "-\\dfrac{" + (-M) + "}{x}" : "\\dfrac{" + M + "}{x}" fractionVariable(1, M, "y") fractionReduce(B, M) fractionReduce(M, B) function( x ) { return M * x + B; } function( x ) { return ( x - B ) / M; } [ [X_OVER_M, "-", B_OVER_M], [M_X, "-", B], [M_X, "+", B], [B_X, "+", M], [M_OVER_X, "+", B], [X_OVER_M, "+", B], [X_OVER_M, "-", B], [X_OVER_M, "-", M_OVER_B], [X_OVER_M, "+", B_OVER_M], [X_OVER_NEG_M, "-", B_OVER_M], [X_OVER_NEG_M, "+", B_OVER_M] ] sanitizeChoices(CHOICES_RAW)

Consider f given by f(x) = M_X + B.

graphInit({ range: 10.8, scale: 20, tickStep: 1, labelStep: 2, }) label( [ 0, 10 ], "{f(x)}", "right" ); label( [ 10, 0 ], "x", "above" ); // draw the function style({ stroke: BLUE, strokeWidth: 2 }, function() { plot( F, [ -11, 11 ] ); });

Find f^{-1}(x) = \ldots

CHOICES[0][0] CHOICES[0][1] CHOICES[0][2]

Start with y = f(x) and solve it for x. This yields to y \mapsto x=f^{-1}(y).

f(x) = y = M_X + B

\implies y + -B = M_X

\implies Y_OVER_M - B_OVER_M = x

\implies x = Y_OVER_M - B_OVER_M.

We know that f^{-1}(y) = Y_OVER_M - B_OVER_M.

var pos = function( n ) { if ( n >= 1 ) { return "below right"; } else if ( n > 0 ) { return "below"; } else if ( n > -1 ) { return "above"; } else { return "above right"; } }, fPos = pos( M ), fInvPos = pos( 1 / M ); // plot function inverse style({ stroke: RED, strokeWidth: 2 }, function() { plot( F_INV, [ -11, 11 ] ); }); if ( M !== -1 && ( M !== 1 || B !== 0 ) ) { // label f style({ color: BLUE, strokeWidth: 1 }, function() { label( labelPos( F ), "f", fPos ); }); // label f_inv style({ color: RED, strokeWidth: 1 }, function() { label( labelPos( F_INV ), "f^{-1}", fInvPos ); }); // Show line of symmetry style({ stroke: "#aaa", strokeWidth: 2, strokeDasharray: "- " }, function() { plot( function( x ) { return x; }, [ -11, 11 ] ); }); }

Rewritting from y to x gives: f^{-1}(x) = X_OVER_M - B_OVER_M.

Note that the graph of f^{-1} is mirroring the graph of f w.r.t. the line y = x.